Drama Techniques in Team Coaching - Marie-Claire Dassen (International Journal of Evidence Based Coaching and Mentoring, 2015)
Team effectiveness and well-being can be negatively affected by unconscious behavioral patterns and dysfunctional group dynamics. Becoming consciously aware of such patterns and understanding their root cause is an important step toward rebuilding a healthy and well-functioning team. When such issues are addressed in a team coaching setting, drama techniques are a powerful tool to help teams understand and improve their functioning. Based on a multiple case study and from a psychodynamic perspective, this article gives an overview of current literature on this topic, formulates criteria found to be conducive to the effective use of such techniques, and describes team coaching qualities helpful in successfully applying these techniques and dealing with group dynamics.